2008
DOI: 10.1038/nature06443
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of critical Casimir forces

Abstract: When fluctuating fields are confined between two surfaces, long range forces arise. A famous example is the quantum electrodynamical Casimir force that results from zero point vacuwn fluctuations confuted between two conducting metal plates'. A thermodynamic analogue is the critical Casimir force: it acts between surfaces immersed in a binary liquid mixture dose to its critical point and arises from the confiuement of con centra tion fluctuations within the thin film of fluid separating the sur faces 2 • So fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
836
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(890 citation statements)
references
References 23 publications
(12 reference statements)
40
836
2
Order By: Relevance
“…[1][2][3][4] While the relaxation time scale of mass diffusion on the micrometer scale is on the order of milliseconds, heat diffusion of water is still typically 3 orders of magnitude faster. Our idea here is to use these faster thermal fields to confine and control the position of molecules despite their thermal motion.…”
mentioning
confidence: 99%
“…[1][2][3][4] While the relaxation time scale of mass diffusion on the micrometer scale is on the order of milliseconds, heat diffusion of water is still typically 3 orders of magnitude faster. Our idea here is to use these faster thermal fields to confine and control the position of molecules despite their thermal motion.…”
mentioning
confidence: 99%
“…The adsorption-induced interaction decays exponentially as exp(−ℓ/ξ) for ℓ ξ if the solvent is at the critical composition without phase separation 8,10,11 , as was measured directly 32 . Some authors 22,27 used this exponential expression to explain the observed aggregation.…”
Section: Introductionmentioning
confidence: 85%
“…In real experiments, charges usually appear on the colloid surfaces in aqueous mixtures 14,15,[18][19][20][21][22]32 . Supposing weak ionization, we neglect the effect of charges on the adsorption-induced interaction.…”
Section: Situations Of Bridgingmentioning
confidence: 99%
“…In the present article we will report theoretical results dealing with the critical Casimir effect. Let us note, that the critical Casimir effect has been already directly observed, utilizing light scattering measurements, in the interaction of a colloid spherical particle with a plate [42] both of which are immersed in a binary liquid mixture. The effect has been also studied in 4 He [43], [44], as well as in 3 He- 4 He mixtures [45] in the context of forces that determine the properties of a film of a substance in the vicinity of its bulk critical point.…”
Section: Introductionmentioning
confidence: 97%